Estrogen ameliorates microglial activation by inhibiting the Kir2.1 inward-rectifier K(+) channel - Wu, Shih-Ying (Sci Rep, 2016)
Microglial activation is implicated in the pathogenesis of Parkinson’s disease (PD). Although the etiology of PD remains unclear, age and male gender are known PD risk factors. By comparing microglia and dopaminergic (DA) neurons in the substantia nigra (SN) of male and female mice of different ages, we found that the degrees of microglial activation and DA neuron loss increased with age in both genders, but were more pronounced in males, as were peripheral lipopolysaccharide (LPS)-induced microglial activation and DA neuron loss. A bilateral ovariectomy (OVX) eliminated the female-associated protection against age- and LPS-induced microglial activation, which suggests that ovary hormones are involved in gender-specific responses. Treating female mice with 17β-estradiol supplements reduced the age-associated microglial activation in OVX mice. Moreover, pretreating mouse BV2 microglial cells with 17β-estradiol inhibited LPS-induced elevation of Toll-like receptor 4, phosphorylated p38, and TNF-α levels. We then examined the effect of 17β-estradiol on inward-rectifier K(+) channel Kir2.1, a known regulator of microglial activation. We found that 17β-estradiol inhibited the Kir2.1 activity of BV2 cells by reducing the probability that the channel would be open. We conclude that age- and inflammation-associated microglial activation is attenuated by ovarian estrogen, because it inhibits Kir2.1.